Financial Factors and Investment in Belgium, France, Germany, and the United Kingdom: A Comparison Using Company Panel Data - Bond, Stephen; Elston, Julie Ann; Mairesse, Jacques; Mulkay, Benoît (The Review of Economics and Statistics, 2003)
We construct company panel data sets for manufacturing firms in Belgium, France, Germany, and the United Kingdom, covering the period 1978–1989. These data sets are used to estimate empirical investment equations, and to investigate the role played by financial factors in each country. A robust finding is that cash flow and profits terms appear to be both statistically and quantitatively more significant in the United Kingdom than in the three continental European countries. This is consistent with the suggestion that financial constraints on investment may be relatively severe in the more market-oriented U.K. financial system.